Efek Enhanced External Counterpulsation Terhadap Perbaikan Kontraktilitas Miokard yang masih viabel pada penderita penyakit jantung koroner - Utojo Lubiantoro; Fadilah Supari; Lies Dina Liastuti (Jurnal Kardiologi Indonesia, 2002)
Objective: To obtain data about the effect of EECP on dysfunctional but viable myocardial contractility in patient with coronary heart disease.Methods: This is an experimental study which include twenty male coronary heart disease but viable myocardium. Before EECP treatment, all subjects under 2D echocardiographic examination and myocardial contractility was measured as WMSI. Patients is given EECP 1 hour daily (5-6 times a week) for a total of 36 hours. Immediately after EECP treatment, WMSI is measured again for each subject. The value between before and after EECP treatment is analyzed with Wilcoxon signed rank test. Significant result if p < 0,05.Results: WMSI decreased after EECP treatment from 1,58+0,39 to 1,53+0,40, but the difference was not significant.Conclusion: EECP does not improve dysfunctional but viable myocardial contractility in patients with coronary heart disease